A novel approach using the five-flap technique for posterior fourchette reconstruction: a clinical study addressing flap deformity and sexual dysfunction - Li, Yilin; Liu, Meichen; Zhou, Yu; Cao, Yujiao; Li, Fengyong (Frontiers in Surgery, 2025)
ObjectiveTo evaluate the clinical efficacy of the five-flap technique in the reconstruction of posterior fourchette flap deformities.MethodsA retrospective analysis was conducted on 36 patients with posterior fourchette flap deformities who underwent surgery using the five-flap technique. Preoperative and postoperative pain scores, sexual function scores, and vulvar aesthetic scores were recorded. Additionally, the degree of sexual function improvement and the incidence of complications were assessed. Depending on the distribution of the data, paired t-tests or non-parametric tests were employed to compare preoperative and postoperative scores. Descriptive statistics summarized the distribution of sexual function improvements and complications.ResultsThe study demonstrated a significant reduction in postoperative pain scores [preoperative: 1.5 [0, 2] vs. postoperative: 0 [0, 1], p = 0.001]. Sexual function scores improved from 19.939 ± 3.903 to 28.742 ± 2.766 (p = 0.019), while aesthetic scores increased from 10.50 (9, 12.75) to 21.72 (20.25, 23) (p < 0.001). Based on the definition of sexual function improvement (significant improvement, moderate improvement, no improvement), 72.2% of patients experienced significant improvement, 25.0% moderate improvement, and only 2.8% showed no improvement. Furthermore, no cases of flap necrosis or recurrence were observed. The complication rate was low, with only one case (2.8%) of mild infection and two cases (5.6%) of scar tension, all of which resolved well with local treatment.ConclusionThe five-flap technique is a safe and effective innovative reconstructive method that demonstrates significant pain relief, sexual function improvement, and aesthetic enhancement in the treatment of posterior fourchette flap deformities. With a low complication rate, it provides a personalized treatment option for complex vulvar deformities.